1987
DOI: 10.1007/bf00120723
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-mediated enhancement of metastasis. Are MHC antigens involved?

Abstract: The relationship between major histocompatibility complex (MHC) antigens and metastasis was investigated on B16 melanoma variants. B16 cell lines express low amounts of murine MHC (H-2) antigens. A high expression can be induced in line B16-A by in vitro treatment with immune interferon (IFN-gamma) or by in vivo transplant in allogeneic mice. The increase of H-2 antigens correlated with an enhancement of lung colonization in young syngeneic mice. The higher metastatic capacity of B16-A cells with induced high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
3
38
2
Order By: Relevance
“…B78H1 murine melanoma cells that are highly resistant to EHV-1 were rendered completely susceptible to EHV-1 infection after expression of the cDNA encoding equine MHC-I. The inability of EHV-1 to infect parental B78H1 cells is most likely explained by the lack of MHC-I receptor expression on these cells (8,33). Likewise, the ability of EHV-1 to infect a diverse array of cells obtained from different species (42) may be explained by the ubiquitous expression of MHC-I receptors on nearly all nucleated cells (5,25) and the structural homology exhibited between MHC-I molecules of different species (25).…”
Section: Discussionmentioning
confidence: 99%
“…B78H1 murine melanoma cells that are highly resistant to EHV-1 were rendered completely susceptible to EHV-1 infection after expression of the cDNA encoding equine MHC-I. The inability of EHV-1 to infect parental B78H1 cells is most likely explained by the lack of MHC-I receptor expression on these cells (8,33). Likewise, the ability of EHV-1 to infect a diverse array of cells obtained from different species (42) may be explained by the ubiquitous expression of MHC-I receptors on nearly all nucleated cells (5,25) and the structural homology exhibited between MHC-I molecules of different species (25).…”
Section: Discussionmentioning
confidence: 99%
“…the immune response being directed against both viral gp70 glycoproteins and a surface tumor antigen (Sala et al, 1992), and we showed that IFN-a transfection of these cells induced a highly effective, long-lasting tumorspecific immunity (Ferrantini et al, 1993). We wanted to know whether the tumorigenicity of a non-immunogenic tumor, such as the murine B16 melanoma (Lollini et al, 1985(Lollini et al, , 1987, could also be decreased by IFN-aI gene expression. After continued passage in vitro, this tumor does not express class-I molecules (Nanni et al, 1993;Lollini et al, 1985), does not confer protection upon animals immunized with irradiated cells (Dranoff et a/., 1993), and grows in and kills allogeneic mice (Nanni et al, 1983;Lollini et al, 1985Lollini et al, , 1987.…”
mentioning
confidence: 99%
“…The metastatic potential of cancer cells was increased also in vivo by using pre-treatments with gamma IFN (Ramani and Balkwill, 1987;Lollini et al, 1987). The enhanced metastasis also correlated to an increase in major histocompatibility complex (MHC) expression (Lollini et al, 1987). Taken together, these data suggest that the enhanced metastatic potential of interferon-treated cells may be related to antigen-inducing effects of interferon in vivo and may also be due to a short exposure of the cancer cells to the drugs.…”
Section: A2058 Cellsmentioning
confidence: 89%
“…Also in agreement with our findings is an investigation by Siegal et al (1982) who showed a considerable enhancement of the invasiveness in vitro of Ewing sarcoma cells treated with IFN alpha and beta. The metastatic potential of cancer cells was increased also in vivo by using pre-treatments with gamma IFN (Ramani and Balkwill, 1987;Lollini et al, 1987). The enhanced metastasis also correlated to an increase in major histocompatibility complex (MHC) expression (Lollini et al, 1987).…”
Section: A2058 Cellsmentioning
confidence: 99%